Analisis Komunitas Online Girl We Can Terkait Efektivitas Komunikasi Interpersonal antara Pengurus dan Anggota - Halim, Danny (Universitas Semarang, 2022)
The Covid-19 pandemic has caused communities that previously worked offline to turn online, and the communities that have been online since the beginning have become more. It also has an impact on the online community of Girl We Can. Changes due to the pandemic require that all activities be carried out virtually, including communication. This study was conducted to determine the effectiveness of interpersonal communication between administrators and members in the Girl We Can. The method used is a qualitative phenomenological approach, and data collection techniques using observation and interviews. The results show that there is still a communication gap between the management and members which has a fatal effect on Girl We Can communication, communication between the management and members is still not effective because of the lack of interaction carried out by the administrators in the Girl We Can WhatsApp group which causes a loss of sense of family and increases sense of individualism. So it s important for the community to increase the quantity of interaction, hold offline meetings, involve community members in internal management, and always pay attention to communication within the community and the needs of members such as member psychology.